Factors associated with rectal colonization by extended-spectrum beta-lactamase-producing Enterobacteriaceae in outpatients in a hospital in northern Peru - Aguilar-Martinez, Sergio Luis (2022)
Background: Extended-spectrum beta-lactamase-producing Enterobacteriaceae (EP-BLEE) are present in the feces of individuals in the community. In Peru, self-medication, type of diet and sanitary conditions could be associated with this colonization. Objective: to determine the frequency of rectal colonization by EP-BLEE in outpatients of the “Hospital Regional Lambayeque”, as well as the factors associated with it, during the months of July 2018 to February 2019. Material and methods: 331 participating patients were interviewed, and three serial samples of freshly emitted stool were obtained from them. The samples were cultured on McConkey agar. EP-BLEE were confirmed with the combined disc test (American method). Results: 85.8% of patients were colonized by EP-BLEE, and Escherichia coli was the most frequent isolate (87.7%). Bivariate analysis associated the consumption of pork (RP=1.15, 95% CI: 1.07 - 1.24), goat (RP=1.18, 95% CI: 1.10 - 1.25) and frequent consumption of salads (RP=1.15, 95% CI: 1.05 - 1.28) with a higher probability of being a rectal carrier of EP-BLEE. Self-medication presented values close to the limit of validity (p=0.051, RP 1.12, 95% CI 0.98 - 1.26). Conclusions: Consuming pork, goat meat and salads increase the probability of being a carrier of EP-BLEE, while self-medication could be associated, so further research is needed, since the reasons for this finding are unknown.